Comparative Analysis of the Labor Market Structure and Active Labor Market Policies of G7 Countries and Turkey Between 2000-2020 - Didem Koca (Sosyal Siyaset Konferansları Dergisi)
The population dynamics in the G7 countries, which represent the seven most developed countries in the world, differ from those in Turkiye. To what extent does this differentiation reflect in their labor market structure and active labor market policies This study descriptively analyzes the labor market structure and ALMPs of the G7 countries and Turkiye for the years 2000-2020 within the scope of this question, which constitutes the basic dynamic of the research. The study aims to analyze the potentials of the G7 countries and Turkiye, which attract attention with regard to changes in their population structures between 2000-2020 and to analyze which countries stand out in terms of active labor market policies with respect to various variables and their advantages and disadvantages in light of the general characteristics of these countries’ labor markets. According to the study results, ALMPs differ with respect to countries’ labor force dynamics. When evaluating active labor market policies according to countries’ GDP, France is seen to excel in education, direct job creation, and job placement practices; Italy in its employment incentives; Germany its job placement practices; and Japan and UK in their workforce skills activation. The most common ALMPs implemented in Turkiye involves training programs.